2020
DOI: 10.1177/2167696820968699
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and LGBTQ Emerging Adults: Risk in the Face of Social Distancing

Abstract: The coronavirus pandemic that began in December 2019 (COVID-19) quickly spread globally with an increased transmission in the United States beginning in March 2020. Social distancing guidelines were instituted across the country, limiting contact individuals could have with others. This compared the mental health of lesbian, gay, bisexual, transgender, and queer (LGBTQ) emerging adults who completed the survey before ( n = 1,190) many social distancing guidelines went into effect with those who completed the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 34 publications
3
32
0
1
Order By: Relevance
“…Presenting a dichotomous view on older immigrants' gender presents an incomplete picture, particularly in light of studies highlighting the double and triple jeopardy faced by sexual minority immigrants and older adults in society and with healthcare systems (Ansara 2015;Dysart-Gale 2010;Wong and Poon 2013). Specifically, during the pandemic, LGBTQ communities have reported greater mental health issues caused by social distancing practices compared to their non-sexual minority counterparts (Scroggs, Love, and Torgerson 2020). Additionally, our findings did not address how gender specifically influences an individual's experiences during lockdown.…”
Section: Limitations and Future Studiesmentioning
confidence: 75%
“…Presenting a dichotomous view on older immigrants' gender presents an incomplete picture, particularly in light of studies highlighting the double and triple jeopardy faced by sexual minority immigrants and older adults in society and with healthcare systems (Ansara 2015;Dysart-Gale 2010;Wong and Poon 2013). Specifically, during the pandemic, LGBTQ communities have reported greater mental health issues caused by social distancing practices compared to their non-sexual minority counterparts (Scroggs, Love, and Torgerson 2020). Additionally, our findings did not address how gender specifically influences an individual's experiences during lockdown.…”
Section: Limitations and Future Studiesmentioning
confidence: 75%
“…Studies among SGM youth and young adults have also revealed that many have concerns about feeling isolated at home with unsupportive families, and have challenges attaining needed social support [ 29 , 30 ]. In an online panel of SGM young adults conducted in March 2020, those recruited after (vs. prior to) the enactment of social distancing guidelines reported lower levels of hope for the future and higher levels of alcohol use [ 31 ]. Furthermore, even prior to the pandemic, SGM (vs. non-SGM) populations were more likely to have insecure employment, to live below the poverty line, and to experience homelessness [ 12 , 13 , 27 ].…”
mentioning
confidence: 99%
“…Quantitative data support these patterns; in one study, 60% of adults with minoritized sexual identities reported that the COVID-19 pandemic had reduced their social contact with friends, and 35% reported reduced connection to the LGBTQ+ community (Suen et al, 2020). Other US-based research suggests that social distancing may be associated with lower community pride in LGBTQ+ emerging adults (Scroggs et al, 2020) and that LGBTQ+ individuals are more likely to feel alone or isolated than cisgender/heterosexual adults (Ruprecht et al, 2021).…”
Section: Social Distancing and Lgbtq+ Mental Healthmentioning
confidence: 97%